Genders and sexualities in educational ethnography - Walford, Geoffrey; Hudson, Caroline (New York : JAI, 2000)
Studies of gender and education have been at the forefront of much ethnographic research for several decades, but the interest in sexualities and education is more recent. Indeed, to study sexualities and schooling is, almost in itself, a challenge to many common assumptions about children and what it is 'to be a child'. However, study of the nature and construction of gender and sexuality has now become a recognized and highly productive research area, and one that is highly suited to ethnographic methods. The new research presented in these chapters illustrates some of the range of recent work in the area and the power of ethnography to uncover the complex and contested processes of construction.
Includes bibliographical references.
Description based on print version record.
Keywords: Gender identity in education -- Great Britain -- Case studies; Sex differences in education -- Great Britain -- Case studies; Educational anthropology -- Case studies; Social & cultural anthropology; Education; Education -- General